Citizenship Education in the Digital Era in Forming Critical Thinking and Participating Through Social Media - Muthia Anggi Amelia (International Journal of Students Education, 2024)
In an increasingly interconnected digital era through social media, the role of civic education becomes ever more crucial in equipping students with the critical thinking skills necessary to navigate the complexities of online information. This research addresses the pivotal role of civic education in shaping students’ critical thinking amidst the dynamics of the digital age. Through an exploration of the interplay between civic education and social media, this paper investigates how civic education curricula can incorporate lessons in digital literacy and online ethics to train students in information evaluation, diverse perspective development, and critical assessment of widely circulated content in the online realm. Furthermore, this study also delves into the potential positive impacts, such as heightened student participation in social and political discourse, which serves as tangible manifestations of an understanding and application of civic values in an era filled with challenges and opportunities. The primary challenge in integrating civic education with social media lies in identifying effective methods for teaching digital literacy and online ethics to students. Additionally, sustained efforts are required to measure the positive impact of this approach on the development of students’ critical thinking skills in the face of the ever-evolving digital landscape. Finally, it is essential to consider how civic education through social media can assist students in comprehending and applying civic values within a broader and more relevant context in their lives.